(untitled) (Journal of Bangladesh Institute of Planners, 2010)
Education is society’s main instrument for reproducing itself and a compelling ingredient for lasting meaningful socio-economic change. Therefore, at the beginning of new millennium, when the United Nations Member States were trying to reach a global consensus on sustainability and development, issues related to universal primary education was a rational choice for them. This paper compares the status quo of this issue between Bangladesh and Peru, where ‘development’ takes place in reality. The increase of universal primary school enrolment is closely related to the national and international spending on education sector for these countries and in addition to this, issues like population growth and spatial poverty traps also put increased pressure on the resources allocation to education. Mostly based on secondary research (e.g. consultation of literature and analysis of indicators on World Development, United Nations Millennium Development Goals and United Nations Children’s Fund Data), this paper highlights the macro level comparative scenario and challenges that these two countries may face in their efforts to achieving universal primary education enrolment targets as part of their UNMDG’s commitments by 2015. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 77-88